2016
DOI: 10.1089/mdr.2015.0306
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization ofStenotrophomonas maltophiliaIsolates from a Brazilian Hospital

Abstract: Stenotrophomonas maltophilia is an emerging nosocomial pathogen responsible for several infections in immunocompromised patients. To characterize the antimicrobial resistance and virulence potential of this microorganism in a Brazilian hospital, a total of 936 samples were collected from a nosocomial environment and medical devices, and 100 isolates from clinical specimens were obtained in the same hospital. S. maltophilia was found in 3% of the samples collected, especially in bed rails from hospital rooms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
1
13
1
1
Order By: Relevance
“…This finding may point the potential patient-bed-patient transmission. Genetic relatedness of clinical and environmental isolates of S. maltophilia was examined using ERIC-PCR by Gallo et al and they found five patterns in both sources (Gallo et al 2016). Also, common PTs of S. maltophilia between environmental and lavage specimens were identified by Ahn et al (2007) in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may point the potential patient-bed-patient transmission. Genetic relatedness of clinical and environmental isolates of S. maltophilia was examined using ERIC-PCR by Gallo et al and they found five patterns in both sources (Gallo et al 2016). Also, common PTs of S. maltophilia between environmental and lavage specimens were identified by Ahn et al (2007) in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…After adhesion, the ability to invade CF-derived IB3-1 bronchial epithelial cells was reported for Sm only, to date [ 81 ], and it represents a way to persist in the CF airways, as intracellular bacteria represent a less accessible reservoir of pathogens for both immune system and antimicrobial agents. Genes, such as the smf -1 gene coding for the fimbrial protein Smf-1, have a crucial role in the bacterial adhesion [ 82 ] and further biofilm formation as only Sm isolates containing the smf -1 gene were found to produce biofilm [ 83 ] ( Figure 1 ). These observations are important for the initial CF patient airway colonization by Axc and Sm via adhesion to the surface of airway mucosae.…”
Section: Pathoadaptive Traitsmentioning
confidence: 99%
“…In the earlier study, clinical isolates from S. maltophilia have been mainly isolated from sputum samples (56.2% of all isolates) (11). Similarly, Gallo SW et al proclaimed that this pathogen was chiefly separated from tracheal aspirate (55%), blood (15.0%) and sputum (14.0%) samples from a Brazilian Hospital (22). However, Kaur et al reported that maximal numbers of strains from blood (61.32%) samples along with respiratory samples (26.41%) (23).…”
Section: Discussionmentioning
confidence: 92%